Penguatan Lisensi Sosial Berusaha di Kelurahan Pasir Putih, Sawangan, Kota Depok - Jannah, Fani Nur; Gunawan, Cecep; Abidin Eko Putro, Moh Zaenal (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2025)
The Rempang incident in Batam in September 2023 proved that rejection of industrial installation by local communities prevails. Learning from this incident, it can be assumed that even the ongoing industry still contains an element of vulnerability regarding its continuation specifically its relationship with the surrounding community. The concept of corporate social responsibility (CSR) is considered unable enough to fully answer the mutual relationship between industry and the surrounding community. In Pasir Putih Village, Sawangan, Depok, there are three natural attractions industries, namely Pondok Zidan, De Kandang, and Pasir Putih Tourist Park. This is where the Publishing Study Program, Graphics and Publishing Engineering Department, Politeknik Negeri Jakarta (Jakarta State Polytechnic) considers it necessary to provide assistance to a group of youth GP Ansor Ranting Pasir Putih as a partner in community service activities to strengthen the integration of local communities and companies or the industrial world which is carried out by utilizing the social license to operate (SLO) theory. The service method is community development (comdev) based on partner problems. The results of this community service include partner communities starting to realize the importance of harmonizing with industry, being able to accept the existence of industry and knowing its role and position in the sustainability of industry in its area.